A 5-year follow-up assessment of anxiety and depression in postoperative prostate cancer patients: longitudinal progression and prognostic value. Issue 2 (7th February 2023) - Li, Xuexin; Zhang, Yuling; Wang, Yanjie
ABSTRACT: Anxiety and depression are prevalent in cancer patients and correlate with poor prognosis. Nevertheless, their clinical role in prostate cancer patients after tumor resection is limited. Thus, the present study aimed to explore the longitudinal progression of anxiety and depression, and their association with prognosis in these patients. Two hundred and sixty-two prostate cancer patients after tumor resection were enrolled. Hospital Anxiety and Depression Scale (HADS) for anxiety (HADS-A) and for depression (HADS-D), disease-free survival (DFS) and overall survival (OS) were documented during 5-year follow-up. HADS-A score (from 7.73 at baseline to 8.48 at 5 years, P = 0.002) and anxiety severity ( P = 0.001) but not anxiety rate (from 37.8% at baseline to 45.4% at 5 years, P = 0.067) were gradually elevated with time. HADS-D score (from 7.43 at baseline to 8.37 at 5 years, P < 0.001), depression rate (from 34.0% at baseline to 46.9% at 5 years, P < 0.001) and depression severity ( P < 0.001) were also obviously increased with time. Moreover, baseline, 1-year, 2-year, 3-year, 4-year and 5-year anxiety correlated with worse DFS and OS (all P < 0.05, except for 2-year anxiety with OS: P = 0.126). In addition, baseline, 1-year, 2-year, 3-year, 4-year and 5-year depression associated with worse DFS (all P < 0.05); while only baseline, 1-year, 2-year depression related to worse OS (all P < 0.05). In conclusion, anxiety and depression continuously aggravate, and associate with poor prognosis in prostate cancer patients after tumor resection, indicating the necessity of proper management of anxiety and depression in these patients.